Generation, Transmission and Application of Orbital Angular Momentum in Optical Fiber: A Review - Ma, Minghao; Lian, Yudong; Wang, Yulei; Lu, Zhiwei (Frontiers in Physics, 2021)
Optical orbital angular momentum (OAM) has become a hot research topic because of its unique properties due to its spiral distribution of phases. The production and transmission of OAM has also become a necessary condition for effective use of OAM. As an optical waveguide with good propagation properties, optical fibers are used in optical systems supporting OAM. This paper introduces the OAM generation and transmission system based on fiber, summarizes the current photonic crystal fiber, ring core fiber, fiber grating and other all-fiber systems that can support OAM modes, and explains some experimental principles. Finally, an outlook on OAM generation or transmission devices for all-fiber systems is presented, providing a useful reference for future related research.